THE ROLE AND CULTURAL DIFFERENCES OF GERMAN AND UZBEK CUISINES IN CULTURE - Turonboyeva X. E. (Modern American Journals, 2025)
The article explores the similarities and differences between German and Uzbek youth from a pedagogical perspective, focusing on their social values, educational priorities, and attitudes toward personal development. As youth represents the most dynamic and transformative segment of society, their worldview and behavior significantly shape the future of both nations. In the modern era of globalization, intercultural communication and digital transformation have brought young people of different regions closer, while preserving distinct cultural identities. The study analyzes theoretical approaches to understanding youth in both countries, considering the impact of educational systems, family models, and social institutions. German youth are generally characterized by individualism, self-reliance, and a high level of civic responsibility, while Uzbek youth tend to maintain collective values, respect for tradition, and strong family ties. The pedagogical systems of both nations play a crucial role in shaping these values through formal and informal education. The article highlights the challenges faced by youth in both contexts, such as digital dependence, labor market uncertainty, and the search for identity in a rapidly changing world. It argues that comparative understanding of youth culture can enhance intercultural competence and pedagogical innovation. The findings suggest that balanced integration of traditional values and modern educational approaches can contribute to forming socially responsible, culturally aware, and creative young generations capable of constructive participation in the global community.
Keywords: Youth, comparative education, pedagogy, cultural values, education system, identity, globalization, socialization.